Labor Market Dynamics and Development - Donovan, Kevin; Lu, Will Jianyu; Schoellman, Todd (Quarterly Journal of Economics, 2023)
Abstract We provide new evidence on how labor market dynamics vary with development. We build a new data set consisting of harmonized microdata from rotating panel labor force surveys covering 80 million people from 49 countries. Labor market flows, such as the job-finding or employment exit rate, are higher in developing economies. These higher flows largely reflect a slippery job ladder: workers transition frequently to and from marginal employment without climbing to or persisting in better-paying jobs. Subsistence self-employment and different patterns of selection for wage workers each play a role in our findings and are useful avenues for future theories of labor market frictions.